Relation of platelet indices to severity of coronary artery disease in patients undergoing primary percutaneous coronary intervention. (April 2016) - Akin, Fatih; Ayca, Burak; Kose, Nuri; Altun, Ibrahim; Avsar, Murat; Celik, Omer; Satilmis, Seckin; Eksik, Abdurrahman; Okuyan, Ertugrul
Aim: We investigated the association between platelet indices and the severity of coronary artery disease (CAD) in patients with ST-segment–elevation myocardial infarction (STEMI) who underwent primary percutaneous coronary intervention (PPCI). Methods: A total of 484 consecutive patients who were routinely referred to coronary angiography for STEMI and 81 age- and gender-matched patients with normal coronary arteries were included in the present study. We analyzed the relation between the platelet distribution width (PDW) and the angiographic severity of CAD. The SYNTAX score was used for assessing the severity of coronary atherosclerosis. Results: The mean platelet volume (MPV), the plateletcrit (PCT) and the neutrophil levels were significantly higher in the STEMI group than in the control group. Patients with an elevated SYNTAX score (>32) had higher PDW values. The levels of plateletcrit and the estimated glomerular filtration rate (eGFR) were lower in the high SYNTAX score group compared to the moderate-to-low SYNTAX score group. The PDW was positively correlated with age (r = 0.128, p=0.004) and SYNTAX score (r = 0.209, p<0.001). There was a mild, significant inverse association between the PDW level and the eGFR (r = -0.101, p=0.049), the mean platelet volume (MPV) (r = −290, p<0.001) and the PCT (r = −345, p<001). Using multivariate logistic regression analysis, we found that age (OR = 1.046, 95% CI 1.013–1.079, p=0.005), diabetes (OR = 4.779, 95% CI 2.339-9.767, p<0.001) and PDW (OR = 1.229, 95% CI 1.072–1409, p=0.003) were independent correlates of high SYNTAX score. Conclusion: Platelet distribution width, an inexpensive and easily measurable laboratory variable, is independently associated with high SYNTAX score.